The Influence Of Grabfood Prices And Promotions On Purchasing Decisions At KFC Kedaton Bandar Lampung During The Covid-19 Pandemic - Wahyu Ageng Laksono; Ardansyah Ardansyah (International Journal of Economics, Business and Innovation Research, 2024)
KFC Kedaton Bandar Lampung collaborates with PT Grab Indonesia to utilize the GrabFood feature to minimize losses during the COVID 19 pandemic. Using the GrabFood feature really helps to increase sales. KFC Kedaton Bandar Lampung utilizes the GrabFood feature to maintain the number of buyers to remain significant or even increase. Through the GrabFood application , the KFC company collaborates with PT Grab Indonesia to provide promotions to attract consumers' attention to make purchases .. The aim of this research is to find out the influence of GrabFood prices and promotions on purchasing decisions at KFC Kedaton Bandar Lampung during the Covid-19 pandemic . This research uses quantitative research methods . Data analysis uses multiple linear regression analysis . Based on the results of the research and discussion, it can be concluded that there is a positive and significant influence of price on purchasing decisions at KFC Kedaton Bandar Lampung, which means Ha is accepted and Ho is rejected, where the better the price the more purchasing decisions at KFC Kedaton Bandar Lampung. There is a positive and significant influence of the Grab Food promotion on purchasing decisions at KFC Kedaton Bandar Lampung, which means Ha is accepted and Ho is rejected, where the better the Grab Food promotion will increase purchasing decisions at KFC Kedaton Bandar Lampung. There is a positive and significant influence on Grab Food prices and promotions Simultaneously there is a purchasing decision at KFC Kedaton Bandar Lampung , which means Ha is accepted and Ho is rejected, where the better the price and promotion of Grab Food will increase the purchasing decision at KFC Kedaton Bandar Lampung .